Potassium in Root Growth and Development - Sustr, Marek; Soukup, Ales; Tylova, Edita (Plants (Basel, Switzerland), 2019)
Potassium is an essential macronutrient that has been partly overshadowed in root science by nitrogen and phosphorus. The current boom in potassium-related studies coincides with an emerging awareness of its importance in plant growth, metabolic functions, stress tolerance, and efficient agriculture. In this review, we summarized recent progress in understanding the role of K+ in root growth, development of root system architecture, cellular functions, and specific plant responses to K+ shortage. K+ transport is crucial for its physiological role. A wide range of K+ transport proteins has developed during evolution and acquired specific functions in plants. There is evidence linking K+ transport with cell expansion, membrane trafficking, auxin homeostasis, cell signaling, and phloem transport. This places K+ among important general regulatory factors of root growth. K+ is a rather mobile element in soil, so the absence of systemic and localized root growth response has been accepted. However, recent research confirms both systemic and localized growth response in Arabidopsis thaliana and highlights K+ uptake as a crucial mechanism for plant stress response. K+-related regulatory mechanisms, K+ transporters, K+ acquisition efficiency, and phenotyping for selection of K+ efficient plants/cultivars are highlighted in this review.
Keywords: deficiency; KT/HAK/KUP transporters; potassium; root growth; root system architecture